1999
DOI: 10.1093/humrep/14.8.2069
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin-releasing hormone antagonists inhibit sperm binding to the human zona pellucida

Abstract: Previous work from our laboratory indicated that gonadotrophin-releasing hormone (GnRH) increases human sperm-zona pellucida binding. Here we present evidence that GnRH antagonists inhibit sperm-zona pellucida binding in humans. Motile spermatozoa (10(7) cells/ml) were incubated in modified Tyrode's medium at 37 degrees C, in 5% CO(2) in air. After 4.5 h, aliquots of spermatozoa were treated with saline (control) or with different concentrations of GnRH antagonists (test). Each sperm aliquot was then tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2000
2000
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
(45 reference statements)
2
14
1
1
Order By: Relevance
“…In accord with this, it was shown that GnRH and GnRH agonists enhanced bovine in vitro fertilization through an effect on the cumulus-oocyte complex [36] and that GnRH increased sperm binding to the human ZP by a direct effect on the sperm cells [37]. Moreover, we have shown that GnRH antagonists inhibited sperm-ZP binding in humans in a dose dependent manner [38]. All these observations allowed us to suggest that human spermatozoa might interact with GnRH (or with GnRH-like molecules) during their journey through the male and female genital tracts and that this interaction with GnRH might confer the spermatozoa increased zona-binding capabilities.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In accord with this, it was shown that GnRH and GnRH agonists enhanced bovine in vitro fertilization through an effect on the cumulus-oocyte complex [36] and that GnRH increased sperm binding to the human ZP by a direct effect on the sperm cells [37]. Moreover, we have shown that GnRH antagonists inhibited sperm-ZP binding in humans in a dose dependent manner [38]. All these observations allowed us to suggest that human spermatozoa might interact with GnRH (or with GnRH-like molecules) during their journey through the male and female genital tracts and that this interaction with GnRH might confer the spermatozoa increased zona-binding capabilities.…”
Section: Introductionsupporting
confidence: 69%
“…As a result of freezing and thawing, these oocytes were never viable. Before use, the oocytes were cut to obtain two equal halves, or hemizonae [37,38,40,42,43].…”
Section: Source and Preparation Of Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports in human and other mammals exist regarding the presence of GnRH receptors in oocytes and spermatozoa (Dekel et al 1988;Minaretzis et al 1995;Morales et al 1999). Increases in the ability of human sperm to bind to the zona pellucida of oocytes when incubated in a medium containing GnRH (Morales 1998), induction of oocyte cleavage by GnRH (Funston and Seidel 1995), stimulation of early embryonic development by a GnRH agonist (Tesarik et al 2004), and a dose-dependent suppression of in vitro fertilization by a GnRH antagonist (Morales et al 1999) support the idea that GnRH has functional significance in regulating processes such as fertilization and early embryonic development, leading to induction of pregnancy in mammals. Expression of immunoreactive GnRH in the human maternal reproductive tract during the luteal phase of the menstrual cycle has been studied (Casan et al 2000), providing evidence of its role as a molecular autocrine/paracrine regulator of processes such as fertilization, early embryonic development, and implantation.…”
mentioning
confidence: 99%
“…Morales [39] a observé in vitro une inhibition de la fixation des spermatozoïdes sur la zone pellucide induite par les antagonistes. Nous n'avons pas retrouvé d'augmentation du taux d'échec total de fécondation en FIV.…”
Section: Discussionunclassified